Astronomische Nachrichten—Broadband photometry of asteroid 6478 Gault: Activity and morphology. Issue 4 (24th June 2020) - Borysenko, Serhii; Baransky, Alexander; Simon, Andrii; Vasylenko, Volodymyr
Abstract: We present the results of a short observational program of asteroid 6478 Gault using of V and R Johnson filters realized at the Kyiv Comet Station during January to April 2019. Color indices and distribution of brightness in the comet‐like tail were calculated. We conducted a comparative analysis of circumstances of the asteroid 6478 Gault activity with others morphologically similar active main‐belt asteroids.